Challenges and Strategies of Digital Literacy in Rural Elementary Schools: A Case Study of SD Negeri 1702 Pir Trans Sosa 1A Padang Lawas Regency - Vika Permata Sari (Jurnal Pendidikan Islam, 2025)
The purpose of this study is to identify barriers and design digital literacy strategies that can be implemented in rural elementary schools. This study is unique because it highlights the under-researched situation in rural elementary schools, specifically SD Negeri 1702 Pir Trans Sosa 1A in Padang Lawas Regency, using a practical approach adapted to the limited facilities. In rural elementary education, the main challenges identified are limited access to information and communication technology, a lack of supporting facilities, and differences in digital skills between rural and urban populations. This study employed a descriptive qualitative method by collecting data through observation, interviews, and document collection. The subjects of the study consisted of teachers, principals, and students involved in the teaching and learning process. Data analysis was conducted using the Miles and Huberman model, which involves data reduction, data presentation, and drawing conclusions. The results show that despite various challenges, there are opportunities to improve digital literacy through several strategic steps, such as conducting regular training for teachers, developing simple digital learning media that can be accessed offline, and establishing active collaboration between schools, parents, and the government. The importance of all parties' roles in creating an educational ecosystem that supports digital literacy was also emphasized. Good digital literacy is expected to increase student participation, develop critical thinking skills, and help them face the challenges of the technological era. With the right strategic support and ongoing collaboration, elementary schools in rural areas can improve students' digital competency and narrow the gap with schools in urban areas.